2021
DOI: 10.1145/3449068
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Pain Protective Behavior Detection with Deep Learning

Abstract: In chronic pain rehabilitation, physiotherapists adapt physical activity to patients’ performance based on their expression of protective behavior, gradually exposing them to feared but harmless and essential everyday activities. As rehabilitation moves outside the clinic, technology should automatically detect such behavior to provide similar support. Previous works have shown the feasibility of automatic protective behavior detection (PBD) within a specific activity. In this article, we investigate the use o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Researchers working on the EmoPain database [6] found that conventional and deep learning methods for analysing human movement are viable tools for detecting pain-related protective behaviours [32], [49], [50]. Wang et al [49], [50], [52] demonstrated that using LSTM-based architectures allows for activity-independent pain-related behaviour detection (PBD) with improved performance. In [49], [50], stacked LSTM and dual-stream LSTM were studied for processing of body movement data in conjunction with data augmentation and segmentation window width approaches.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Researchers working on the EmoPain database [6] found that conventional and deep learning methods for analysing human movement are viable tools for detecting pain-related protective behaviours [32], [49], [50]. Wang et al [49], [50], [52] demonstrated that using LSTM-based architectures allows for activity-independent pain-related behaviour detection (PBD) with improved performance. In [49], [50], stacked LSTM and dual-stream LSTM were studied for processing of body movement data in conjunction with data augmentation and segmentation window width approaches.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Wang et al [49], [50], [52] demonstrated that using LSTM-based architectures allows for activity-independent pain-related behaviour detection (PBD) with improved performance. In [49], [50], stacked LSTM and dual-stream LSTM were studied for processing of body movement data in conjunction with data augmentation and segmentation window width approaches. Three LSTM layers and two sets of three LSTM layers (for the MoCap and sEMG streams) were used for stacked-LSTM and dual-stream LSTM, respectively.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Rashid et al [59] presented a data-augmentation framework for generating synthetic time-series training data for an RNN-based deep learning network to accurately and reliably recognize equipment activities. Wang et al [60][61][62] used an augmentation method of jittering and cropping to increase the performance of automatic protective behavior detection. Gao et al [63] presented several data augmentation techniques specifically designed for time-series data in both the time domain and frequency domain.…”
Section: Related Workmentioning
confidence: 99%
“…As digital cameras and motion sensors became ubiquitous and are commonly used in mobile phones and office environments, various MSD detection methods have been developed based on commercially available devices [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. Along with this, various resources have been created, including datasets made with cameras [13][14][15][16][17][18][19], wearable motion capture sensors [20][21][22][23], Kinect devices [17,[24][25][26][27], and many others.…”
Section: Introductionmentioning
confidence: 99%